Comment créer une tragédie moderne de construction classique ? Jeux avec les règles - Starak, Grażyna (Romanica Silesiana)
The output of dramatic works of Bernard-Marie Koltès in the 1970s and the 1980s shows remarkable richness of invention as far as the construction of the works is concerned. The fondness of research and experiment led the author of In the Solitude of Cotton Fields from the monologue or quasi-monologue, through sophisticated forms which resembled the eighteenth century philosophical Dialogue à la Diderot, up to the much more complex structures, such as those of Roberto Zucco. The choice of form was determined in a way, as the author maintained, by the play itself (“Chacune de mes pièces m’impose ses propres contraintes”). Interesting in that respect is the play Combat de nègre et de chiens, whose originality lies, paradoxically, in its evocation of a classical construction, with all the resulting consequences and limitations concerning the structure, time, place, the content of action, the number of characters etc. The tragedy with the classical construction became, however, a very modern play, and it was not only because of the date of its origin. It was so because of a few measures applied by Koltès. And it is the analysis of these measures, i.e. the “games” played by classical rules, which is going to be the subject matter of this article. Key words: Form, tragedy, rules, modernity, games.